2018
DOI: 10.1111/jocn.14064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nurse‐led transitional care programme on readmission, self‐efficacy to implement health‐promoting behaviours, functional status and life quality among Chinese patients with coronary artery disease: A randomised controlled trial

Abstract: The nurse-led transitional care programme is helpful for coronary artery disease patients to promote their effective transfer from hospital to community and provide an evidence for nursing managers to train their nurses for transitional care knowledge and skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(96 citation statements)
references
References 32 publications
4
89
0
3
Order By: Relevance
“…The results showed that the readmission rates were not statistically significant in the two groups after 2 months, but the rates in the intervention group was lower when compared with the control group. This is consistent with the findings of previous studies as per which transitional care model is insufficient to control the readmission rates at a significant level (Wong & Yeung, 2015;Zhang et al, 2018). It can be inferred that transitional care interventions can effectively raise the awareness of patients with self-management diseases and help them actively seek medical assistance (Zhao & Wong, 2009).…”
Section: Effectiveness Of Nurse-led Tcp On Hospital Readmissionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results showed that the readmission rates were not statistically significant in the two groups after 2 months, but the rates in the intervention group was lower when compared with the control group. This is consistent with the findings of previous studies as per which transitional care model is insufficient to control the readmission rates at a significant level (Wong & Yeung, 2015;Zhang et al, 2018). It can be inferred that transitional care interventions can effectively raise the awareness of patients with self-management diseases and help them actively seek medical assistance (Zhao & Wong, 2009).…”
Section: Effectiveness Of Nurse-led Tcp On Hospital Readmissionsupporting
confidence: 90%
“…The Omaha System is an effective tool for assessing patient health issues and providing nursing interventions as well as effectiveness evaluations from a holistic approach. This system applies to patients with all ages, diseases, cultural backgrounds, religious beliefs, and socioeconomic status (Erci, 2012;Monsen, Holland, Fung-Houger, & Vanderboom, 2014;Topaz, Golfenshtein, & Bowles, 2014;Zhang, Xing, Li, Wang, & Zhang, 2018). A large number of studies have shown that implementing the Omaha system in TCP can drastically improve the quality of care and self-management of patients with chronic diseases (Erci, 2012;Monsen et al, 2014;Topaz et al, 2014;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a systematic review and meta-analysis, nursing activities such as home visits, case management, and disease management clinics where physicians and cardiac nurses work together with a multidisciplinary HF management team showed significantly decreased all-cause readmission and death [9]. Moreover, in some interventions for heart diseases, the effects of nurse-led transitional care programs appeared excellent [16,48]. We confirmed that nurses are the most important healthcare providers of transitional care for patients with HF.…”
Section: Discussionsupporting
confidence: 57%